Development of Papuan Culture-Based Literature Materials for Explanatory Text Learning - Adi Iwan Hermawan; Ernawati Simatupang; Batsheba Gela; Rashikah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2024)
Reading and literary literacy in Indonesia's eastern regions, particularly in Southwest Papua Province, remains at a very low level, with the reading literacy activity index recorded at 19.90 for Papua and 28.25 for Southwest Papua, both of which fall into the low to very low categories. This condition contributes to a low Human Development Index and is closely tied to the many 3T (frontier, outermost, disadvantaged) areas found within the province, one of which is SD Inpres 138 Wardik in South Sorong Regency. This study aims to develop a literature literacy teaching material containing Papuan culture, namely BASASTRA, to support the learning of explanatory texts and to examine its validity and practicality. The study used a Research and Development (R&D) approach with the Plomp model, consisting of preliminary investigation, design, realization/construction, test-evaluation-revision, and implementation phases. Data were collected through interviews, questionnaires, observation, and documentation involving a classroom teacher, twelve sixth-grade students, and three validators (language, material, and teaching material experts). The results show that the need for a culturally-based literature teaching material reached an average of 84% (very needed). Expert validation results indicated that the developed material was very valid, with language, material, and teaching material aspects scoring 89%, 96%, and 95% respectively. Trial results also showed that the material was very practical, with student and teacher responses reaching 92% and 87%. These findings confirm that a literature literacy teaching material integrated with local Papuan culture can meet the needs of teachers and students in 3T elementary schools and can be considered a valid and practical learning resource for explanatory text material.